2021
DOI: 10.3390/toxins13010034
|View full text |Cite
|
Sign up to set email alerts
|

Using Cholinesterases and Immobilized Luminescent Photobacteria for the Express-Analysis of Mycotoxins and Estimating the Efficiency of Their Enzymatic Hydrolysis

Abstract: Novel sensitive analytical agents that can be used for simple, affordable, and rapid analysis of mycotoxins are urgently needed in scientific practice, especially for the screening of perspective bio-destructors of the toxic contaminants. We compared the characteristics of a rapid quantitative analysis of different mycotoxins (deoxynivalenol, ochratoxin A, patulin, sterigmatocystin, and zearalenone) using acetyl-, butyrylcholinesterases and photobacterial strains of luminescent cells in the current study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…However, they can be accompanied by the accumulation of toxic intermediates. The degradation of mycotoxins using biological strategies is a promising solution to the problem of mycotoxins, since it can result in the formation of small amounts of toxic products or their complete absence [ 5 , 10 ]. The disadvantage of biocatalytic methods of mycotoxin degradation is a long period of necessary treatment (15–100% degradation is achieved within 25–60 days, Table 4 ).…”
Section: Expected Potential In Development Of Anaerobic Biocatalysts ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they can be accompanied by the accumulation of toxic intermediates. The degradation of mycotoxins using biological strategies is a promising solution to the problem of mycotoxins, since it can result in the formation of small amounts of toxic products or their complete absence [ 5 , 10 ]. The disadvantage of biocatalytic methods of mycotoxin degradation is a long period of necessary treatment (15–100% degradation is achieved within 25–60 days, Table 4 ).…”
Section: Expected Potential In Development Of Anaerobic Biocatalysts ...mentioning
confidence: 99%
“…Today, the attention of many researchers in the world is focused on the study of problems related to the prevention of mycotoxin contamination of food and pharmaceutical products and animal feed. To date, a significant progress has already been made in this direction: the structures of mycotoxins were established [ 1 ], their mechanisms of actions were revealed [ 1 , 2 ], methods of their detection and identification were elaborated [ 3 , 4 , 5 , 6 ], and approaches to their detoxification were developed inside of various materials [ 7 , 8 , 9 ] and in vivo (in the body of animals) [ 10 ]. However, large volumes of organic wastes containing mycotoxins, in particular coming from agriculture, compose new tasks related to the need to solve environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Once the artificial consortium has been formed, the anaerobic microorganisms of such consortium can be gradually adapted to the presence of components which are otherwise toxic for these cells [126]. The toxicity of the extracts before introducing them into the bioreactor can be evaluated via a bioanalytical technique using PVA cryogel-immobilized Photobacterium cells [171][172][173][174]. An optimal solution concentration for the extracts can be chosen, if necessary, to minimize the inhibiting effect of the chemical components therein on the biocatalytic activity of the participants of the microbial consortium [24].…”
Section: Specialized Adaptive and Complex Approaches To Involving Ibcs In Hybrid Ods Processesmentioning
confidence: 99%
“…Generally, both methods give a quick response to the presence of toxic compounds. In our previous comparative investigation of choline esterase and immobilized luminous bacteria Photobacterium phosphoreum [19] in the detection of four mycotoxins, it was established that biosensors on the basis of photobacterial cells had better analytical characteristics. Moreover, it was shown that the cells can be applied for the estimation of the resulting toxicity of the medium obtained after the hydrolytic reaction of hexahistidine-tagged organophosphorus hydrolase with zearalenone.…”
Section: Introductionmentioning
confidence: 99%